Avaliação de biomarcadores convencionais de dano renal e dos níveis de MCP-1 e Nefrina em recém-nascidos portadores de sífilis congênita: correlação com os títulos de VDRL - Dantas, Suzzy Maria Carvalho (2023)
Kidney damage is one of the complications associated with congenital syphilis (CS), with glomerulonephritis being the main manifestation, favorable for the increase in morbidity and mortality rates, especially in premature newborns (NB). It is noteworthy that the diagnosis of CS consists of evaluating the maternal history, clinical signs and symptoms, and the NB's VDRL title compared to the mother's. Due to the difficulties inherent to conventional renal function markers in this population, it is necessary to research biomarkers that do not suffer interference from maternal biomarkers such as MCP-1 and nephrin, related to both glomerular and tubulointerstitial damage. The aim of the study was to evaluate conventional and innovative biomarkers of kidney damage in NBs with CS and to correlate them with VDRL titers. This is a cross-sectional, observational and analytical study involving 77 NBs, 52 diagnosed with CS and 25 normal, from the Maternidade Assis Chateaubriand (MEAC), Fortaleza, Ceará. Chronic creatinine, albuminuria and proteinuria levels were measured by integrated immunoturbidimetry and MCP-1 and nephrin by immunoassay. The clinical and laboratory data of the NBs and sociodemographic and prenatal data of the mothers were obtained from medical records. The statistical program SPSS was used with a significance level of 5% (p<0.05). Most NBs were male, median gestational age of 38 weeks and 3 days, 70 (90.9%) full term and 7 (9.1%) premature, mean weight of 3165.8g ± 493.4, being 66 (85.71%) adequate for gestational age, 4 (5.2%) small for gestational age and 7 (9.1%) large for gestational age. Ten (19.23%) of the NBs in the SC group presented symptoms, the remaining 42 (80.77%) were asymptomatic. There was no statistical difference between the APGAR and temperature of the evaluated newborns. Only 1 NB with CS presented malformation. The mothers had an average age of 24 years, most from the city of Fortaleza, 50 (64.93%) were married or had a stable relationship, 25 (32.46%) were single. A total of 47 (61.03%) mothers had a normal delivery. The average number of pregnancies was equal to 2. A total of 16 (20.77%) mothers had a history of abortion and 3 (3.89%) did not receive prenatal care. The average of consultations was seven. There was no statistical difference regarding age, marital status, type of delivery, gestational history, prenatal care or number of consultations between mothers of NBs with CS and controls. The chi-square test showed a significant association between titles greater than 1:4 and mothers in the SC group. The association of substance use (alcohol, tobacco, narcotics) during pregnancy with the group of mothers of NBs with CS was verified. As for the sociodemographic profile of the mothers in the study, only 30 (38.96%) were housemaids, 30 (38.96%) mothers had completed elementary school, 42 (54.54%) high school, 2 (2.59%) %) incomplete higher education, 1 (1.29%) without schooling. There was no significant association with regard to education or professional occupation status between the evaluated groups. There was no statistical difference between the medians of proteinuria biomarkers (mg/mgCr): (0.52 and 0.48); albuminuria (mg/gCr): 103.84 and 82.65; MCP-1 (pg/mgCr): 729.1 and 955.3; and nephrine (pg/mgCr ): 0 and 0, between the groups of control and CS NBs, respectively. Regarding the evaluation of the dynamics of VDRL titers with biomarkers of renal function in the group of NBs with CS, a positive result was found for VDRL titers with albuminuria (r=0.850; p<0.001), with proteinuria (r= 0.764 ; p<0.001) and with uMCP-1 (r=0.292; p=0.044). In the evaluation of immunology among the biomarkers of renal damage, the positive defense between Albuminuria and uMCP-1 (r=0.500; p=0.001), Albuminuria and proteinuria (r=0.973; p<0.001), proteinuria and uMCP-1 (r=0.525; p<0.001). There was no transpiration of uNephrine with the VDRL titers, nor with the other biomarkers. The results showed that there was no difference between the biomarkers evaluated in the groups under study, but it was tolerated that they, even without apparent kidney damage, changed early in the population with CS according to the increase in VDRL titers, therefore prospective studies are necessary to assess actual renal impairment.